PENGARUH VARIABEL MAKROEKONOMI TERHADAP EKSPOR KAYU OLAHAN INDUSTRI INDONESIA KE AUSTRALIA TAHUN 2000-2019 - Andi Putri Ramadhani Musa; Syamsu Alam; Ridwan (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Macroeconomic variables influence the sustainability of export activities, so it is considered necessary to identify the macroeconomic variables that affect exports and to know the direction and magnitude of the influence of the variables on the export of industrial processed wood from Indonesia to Australia. Secondary data from official sources from 2000 to 2019 were analyzed using multiple linear regression in logarithm form. The results obtained on the variable plywood population, price, and exchange rate of the rupiah have a positive effect, negative GDP and R Square 65.6%. For sawn wood, GDP and the rupiah exchange rate have a positive effect, population and price have a negative effect with R Squared 81.1%. In the veneer, the variable GDP has a positive effect, the population, the price, and the exchange rate of the rupiah have a negative effect and the R squared is 41.8%.